2006
DOI: 10.1002/elsc.200620904
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Engineering Aspects of Microbial Mercury Removal

Abstract: Mercury‐resistant microorganisms are widespread in natural environments and can effectively be used to demercurize Hg(II)‐contaminated wastewaters as was already demonstrated on an industrial scale. The aim of this paper is to find the performance limits with regard to Hg(II) loadings D cHg,in (dilution rate × Hg(II) inlet concentration) and residual Hg(II) at the reactor outlet and to provide a reasonable basis for an optimal and safe process design. To this end, comprehensive studies were carried out with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…These adsorption results are in agreement with those found with another P. putida strain (Chang and Hong, 1994). Analysis of effluent streams from a 1 m³ fixed bed bioreactor also showed that dissolved elemental mercury concentrations in the effluent were very low (< 5%), while 60-80% of the mercury was bound to biomass (Leonhäuser et al, 2006).…”
Section: Resultssupporting
confidence: 80%
“…These adsorption results are in agreement with those found with another P. putida strain (Chang and Hong, 1994). Analysis of effluent streams from a 1 m³ fixed bed bioreactor also showed that dissolved elemental mercury concentrations in the effluent were very low (< 5%), while 60-80% of the mercury was bound to biomass (Leonhäuser et al, 2006).…”
Section: Resultssupporting
confidence: 80%
“…The binding of metal ions with supported biofilms is relayed by several authors: Quintelas and Tavares [12,13] used a biofilm of Arthrobacter viscosus to remove Cr(VI), Cd(II), Pb(II) and Fe(II), Kang et al [14] applied a biofilm of Pseudomonas aeruginosa to the removal of Cr(III), Ni(II) and Co(II), Leonhauser et al [15] studied the behaviour of a biofilm of A. hydrophila and P. putida in mercury removal. The bacterial extracellular polymeric substances (EPS) synthesis is an aspect of special relevance in the development of biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…[20] However, other significant sources of pollution can be also mentioned, such as the use of mercury as cathode in the chloralkali industrial electrolysis at large scale leading to significant mercury emissions (ca. 1 g Hg/t chlorine [21] ;), and highly polluted wastewater (up to 7.6 mg L À1 , [22] ). Mercury is also used in numerous industrial and medical applications (fungicides, disinfectants, dental products, catalysts, igniters, dyes production, etc.).…”
Section: Recombinant Protein Productionmentioning
confidence: 99%